Arthroscopic Fixation and Ligament Reconstruction in Tibial Plateau Fracture: A Case Report (London Journal of Medical and Health Research, 2025)
Introduction: Tibial plateau fractures account for approximately 1% of all fractures; however, they are associated with high morbidity due to a wide spectrum of soft tissue injuries and a significant incidence of concomitant ligamentous and meniscal lesions. Among these, anterior cruciate ligament (ACL) injuries are particularly relevant, as delayed diagnosis or inadequate management of these injuries can compromise joint stability and long-term functional outcomes.Case presentation: We present the case of a 33-year-old male patient with a lateral tibial plateau fracture (Schatzker type I) associated with a complete anterior cruciate ligament tear and a fibular head fracture in the right knee following a traffic accident. The patient underwent ACL reconstruction using hamstring tendon autograft, along with open reduction and internal fixation of the tibial plateau and fibular head fractures. Postoperative evolution has been satisfactory, with full recovery of range of motion, a stable, pain-free knee, and favorable functional outcomes.Discussion: Tibial plateau fractures are complex articular injuries with a high incidence of associated ligamentous damage, particularly involving the anterior cruciate ligament. Treatment should be individualized based on the fracture pattern and associated injuries. Arthroscopy-assisted techniques represent a viable option for reduction, fixation, and simultaneous management of intra articular lesions, contributing to joint function preservation and showing satisfactory functional outcomes.Conclusion: This case highlights the importance of maintaining a high index of suspicion for associated ligament injuries in tibial plateau fractures, regardless of the fracture pattern. Additionally, the arthroscopy-assisted approach is emphasized as a valuable tool for achieving precise anatomic reduction and simultaneous anterior cruciate ligament (ACL) reconstruction in a single surgical procedure. The case presented, along with the available evidence, supports the combined approach as a safe, effective, and minimally invasive strategy that promotes early functional recovery and favorable clinical outcomes.
Keywords: Depression; antidepressants; pharmaceutical industry; psychiatric drug research; guillain barre syndrome; Chikungunya; Peripheral neuropathies; Arboviruses.; Tibial plateau fracture; anterior cruciate ligament injury; arthroscopic surgery; ligament reconstruction